Polyhydroxyalkanoate (PHA) synthase genes and PHA-associated gene clusters in Pseudomonas spp. and Janthinobacterium spp. isolated from Antarctica - Tan, Irene Kit Ping; Foong, Choon Pin; Tan, Hua Tiang; Lim, Hui; Zain, Noor Afiqah Ahmad; Tan, Yung Chie; Hoh, Chee Choong; Sudesh, Kumar (Elsevier, 2020)
The polyhydroxyalkanoate (PHA) producing capability of four bacterial strains isolated from Antarctica was reported in a previous study. This study analyzed the PHA synthase genes and the PHA-associated gene clusters from the two antarctic Pseudomonas isolates (UMAB-08 and UMAB-40) and the two antarctic Janthinobacterium isolates (UMAB-56 and UMAB-60) through whole-genome sequence analysis. The Pseudomonas isolates were found to carry PHA synthase genes which fall into two different PHA gene clusters, namely Class I and Class II, which are involved in the biosynthesis of short-chain-length-PHA (SCL-PHA) and medium-chain-length-PHA (MCL-PHA), respectively. On the other hand, the Janthinobacterium isolates carry a Class I and an uncharacterized putative PHA synthase genes. No other gene involved in PHA synthesis was detected in close proximity to the uncharacterized putative PHA synthase gene in the Janthinobacterium isolates, therefore it falls into a separate clade from the ordinary Class I, II, III and IV clades of PHA synthase (PhaC) phylogenetic tree. Multiple sequence alignment showed that the uncharacterized putative PHA synthase gene contains all the highly conserved amino acid residues and the proposed catalytic triad of PHA synthase. PHA biosynthesis and in vitro PhaC enzymatic assay results showed that this uncharacterized putative PHA synthase from Janthinobacterium sp. UMAB-60 is funtional. This report adds new knowledge to the PHA synthase database as we describe scarce information of PHA synthase genes and PHA-associated gene clusters from the antarctic bacterial isolates (extreme and geographically isolated environment) and comparing with those from non-antarctic PHA-producing bacteria. © 2020 Elsevier B.V.